2014
DOI: 10.14314/polimery.2014.302
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thermal properties of isotactic polypropylene with different additives during aging process

Abstract: Polymer degradation is a change in the properties of a polymer under the influence of one or more environmental factors such as heat, light, humidity or chemicals. These changes may be undesirable, such as changes during use, or desirable, as in biodegradation or deliberately lowering the molecular weight of a polymer. A series of composites of isotactic polypropylene (iPP) has been obtained by the melt intercalation by introducing certain additive into the molten polymer matrix using a twin-screw extruder. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 3 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…The next clearly visible peak is an endothermic peak with onset and maximum values at 157 • C and 163 • C, respectively. The enthalpy of this peak is 60.59 J/g, which corresponds to a crystallinity of around 28%, assuming ∆H100% equals 207 J/g [20]. The low degree of crystallinity testifies that the addition of powdered materials such as SAP and Biohaloysite do not result in significant crystallization in the melt-blow processing of PP.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 97%
“…The next clearly visible peak is an endothermic peak with onset and maximum values at 157 • C and 163 • C, respectively. The enthalpy of this peak is 60.59 J/g, which corresponds to a crystallinity of around 28%, assuming ∆H100% equals 207 J/g [20]. The low degree of crystallinity testifies that the addition of powdered materials such as SAP and Biohaloysite do not result in significant crystallization in the melt-blow processing of PP.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 97%
“…In addition to that, in co-pyrolysis, the drop of temperature occurred in part due to heat absorption by PP melting. Brzozowska-Stanuch et al [41] found that polypropylene has a melting point of 163 • C and it requires heat for melting. Figure 4 shows that there was a large curve bump within the range of about 200-350 °C on biomass spheres.…”
Section: Comparison Of Temperatures Of Biomass Spheres and Pyrolysis mentioning
confidence: 99%
“…In previous research, the concentration of metal salts with synthetic polymer blends was varied up to 0.2 wt % as the authors concluded that only small percentage of Transition Metal Stearates (TMS) could alter the mechanical properties and cause thermooxidative degradation in a synthetic plastic . However, there have also been contradictory findings that have explained that only a larger amount of additives will modify the mechanical properties of pure polymers . In this study, PP was blended with metal additives, including cobalt stearate (CoSt 2 ) and iron stearate (FeSt 3 ), at up to 0.9 wt % to form PP–metal additive blends.…”
Section: Introductionmentioning
confidence: 99%